First-principles calculations of mechanical, optoelectronic, and thermal properties of double perovskite K2GeCl/Br6 for solar cell applications. (December 2021) - Ali, A.; Karim, Altaf; Rashid, Muhammad; Aljameel, A.I.; Albalawi, Hind; Morsi, Manal; Bouzgarrou, S; Mahmood, Q.
Abstract: In this study, we investigated the crystal structure and mechanical, electronic, optical, and transport properties of K2 GeCl/Br6 using the modified Becke–Johnson potential. The structural and mechanical stability were determined based on the tolerance factor and elastic constants. The ductile nature was verified according to the Poisson's ( v ) and Pugh's ( B 0 /G ) ratios. Optoelectronic analysis showed that K2 GeCl/Br6 compounds are suitable for solar cell applications because of their direct band gaps (2.92 eV and 1.60 eV, respectively) and large absorption coefficient values in the ultraviolet and visible regions. The absorption bands from 563 nm to 387 nm and 354 nm–275 nm are extremely important for visible and ultraviolet light applications, respectively. The spin–orbit coupling reduced the negligible band gap due to the deep levels of K. The refractive indices of these compounds were also determined based on the incident photon energy. Moreover, the figure of merit values were calculated as 0.755 and 0.76 at room temperature, thereby demonstrating the potential uses of these materials in thermoelectric applications. Highlights: Alternative organic–inorganic and Lead free perovskites. Absorption in visible region enhances their potential uses in solar cells. Minimum optical loss and reflectivity. High thermodynamic and structural stability. Low thermal conductivity and high figure of merit.